Odpowiedź :
a)
[tex]x(x^2-36)(5x+2)=0\\\\x(x+6)(x-6)(5x+2)=0\\\\\boxed{x_1=0}\\\\x+6=0\longrightarrow\boxed{x_2=-6}\\\\x-6=0\longrightarrow\boxed{x_3=6}\\\\5x+2=0\longrightarrow\boxed{x_4=-0,4}[/tex]
b)
[tex]x^2(x^3+64)(x^2+4)=0\\\\x^2=0\longrightarrow\boxed{x_1=0}\\\\x^3+64=0\longrightarrow x=\sqrt[3]{-64}\longrightarrow\boxed{x_2=-4}\\\\x^2+4=0\longrightarrow x^2=-4 \ (\text{sprzeczne!})[/tex]
c)
[tex]x^3-6x^2-7x=0\\\\x(x^2-6x-7)=0\\\\\boxed{x_1=0}\\\\x^2-6x-7=0\\\\a=1, \ b=-6, \ c=-7\\\\\Delta=b^2-4ac\rightarrow(-6)^2-4\cdot1\cdot(-7)=36+28=64\\\\\sqrt{\Delta}=\sqrt{64}=8\\\\x_2=\frac{-b-\sqrt{\Delta}}{2a}\rightarrow\frac{-(-6)-8}{2\cdot1}=\frac{6-8}{2}=\frac{-2}{2}=\boxed{-1}\\\\x_3=\frac{-b+\sqrt{\Delta}}{2a}\rightarrow\frac{-(-6)+8}{2\cdot1}=\frac{6+8}{2}=\frac{14}{2}=\boxed7[/tex]